Visualising relational values in a region: how two conservation stakeholder groups in the US Northwest conceive of their relationships with the land - Timothy Pape (Regional Studies, Regional Science, 2023)
ABSTRACTMany conservation programmes pay property owners for land use practices which deliver certain ecosystem services, yet there can be enrolment challenges. Consequently, this paper visualises how two stakeholder groups in the US Northwest involved with a conservation programme (enrollers and enrolees) conceive of their relationships with the land. This regional graphic is an example for how to visually express complex qualitative data in an accessible fashion using geographic and tag cloud methodologies. Graphics of this type can be used to improve understanding of the variety of ways that people value nature at the public-private nexus of conservation.